Simulation study on the performance of a counter-rotating savonius vertical axis wind turbine - Didane, Djamal Hissein; Saipul Anuar, Muhammad Amir Zafran; Mohideen Batcha, Mohd Faizal; Abdullah, Kamil; Mohd Ali, Mas Fawzi; Mohammed, Akmal Nizam (Penerbit Akademia Baru, 2020)
Wind power is an energy source that is becoming an alternative to burning fossil fuels that may harm the environment during operations due to the emission of harmful gases. In this study, simulation and performance investigations of a counter-rotating vertical axis wind turbine (VAWT) based on the Savonius S-type rotor have been analysed through a computational simulation approach. The foremost motive of this study is to widen the operating wind speed range of the counter-rotating concept in a VAWT while enhancing the conversion efficiency of a single-rotor VAWT system. The 3D simulations were performed based on the K-omega shear stress transport (SST) turbulence model. The results have shown that the counter-rotating model possesses better performance characteristics in terms of torque, power and their corresponding coefficients compared to a single-rotor design of a wind turbine. A maximum output of more than two times was obtained from the new CRWT system compared to that of a single-rotor wind turbine (SRWT). Moreover, the output of the top rotor was higher than the bottom rotor due to the increased higher rotational speed of the top rotor.